Показники ліпідного обміну у пацієнтів із хронічною серцевою недостатністю на тлі надлишкової маси тіла і ожиріння залежно від тяжкості захворювання - Бідзіля, Петро Петрович; Бидзиля, П. П.; Bidzilya, P. P. (ОНМУ, 2016)
Целью работы было изучение изменений показателей липидного обмена у пациентов с хронической сердечной недостаточностью (ХСН) и избыточной массой в зависимости от тяжести заболевания. Установлено, что повышение функционального класса ХСН при избыточной массе тела и ожирении характеризуется снижением уровня атерогенных и антиатерогенных показателей липидного обмена. Выявленные изменения сопровождаются уменьшением частоты наблюдения высоких уровней атерогенных показателей и увеличением частоты выявления низкого уровня антиатерогенного холестерина липопротеина высокой плотности. Не отмечалось достоверных отличий при ХСН с сохраненной и сниженной фракцией выброса левого желудочка. In recent time, there appear a number of works which found that low cholesterol is a predictor of progression and negative effects in existing chronic heart failure (CHF). In contrast, high levels of lipids in the blood were associated with better course and survival in CHF patients. The level of lipids has an inverse correlation with the severity of CHF. The aim is the studying parameters of lipid metabolism in patients with CHF on the background of overweight and obesity depending on severity of the disease. Materials and methods. There were examined 210 patients with CHF I–III functional class (FC) by NYHA, with normal and overweight, and obesity I–III degree. The study included patients with CHF due to chronic forms of ischemic heart disease (stable angina, post-myocardial infarction and diffuse cardiosclerosis), arterial hypertension and/or their combination. The patients underwent biochemical blood tests with the definition of lipid metabolism components and their ratios. Results and discussion. It is established that the increase FC of CHF in overweight and obesity characterized by a decrease in the level of atherogenic and antiatherogenic components of lipid metabolism. The revealed changes are accompanied by a decrease in the frequency of observation of high levels of atherogenic indicators and increase the detection rate of low level of antiatherogenic highdensity lipoprotein cholesterol. There are no significant differences in CHF patients with preserved and reduced left ventricle ejection fraction.
Показатели липидного обмена у пациентов с хронической сердечной недостаточностью на фоне избыточной массы тела и ожирения в зависимости от тяжести заболевания
Parameters of lipid metabolism in patients with chronic heart failure on the background of overweight and obesity depending on the severity of the disease
Keywords: липидный обмен; избыточная масса тела; сердечная недостаточность; тяжесть заболевания; lipid metabolism; heart failure; severity; excess weight